2020
DOI: 10.1111/jan.14610
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and self‐management behaviours among patients with chronic hepatitis B receiving oral antiviral therapy

Abstract: Aims To assess the prevalence and associated factors of psychological distress among patients with chronic hepatitis B receiving oral antiviral therapy and explore the association between psychological distress and self‐management behaviours among this population. Design A cross‐sectional study. Methods A convenience sample of 188 patients with chronic hepatitis B receiving oral antiviral therapy was recruited from March‐October 2018 to complete a self‐report questionnaire including the Chinese version of Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Moreover, patients with CHB usually experienced psychological distress. 3 , 4 Patients with higher self-efficacy tend to be more capable of dealing with disease demands and are less affected by negative emotions, benefiting their QoL. Our results further highlight that self-efficacy could be a useful intervention target for improving QoL among patients with CHB.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Moreover, patients with CHB usually experienced psychological distress. 3 , 4 Patients with higher self-efficacy tend to be more capable of dealing with disease demands and are less affected by negative emotions, benefiting their QoL. Our results further highlight that self-efficacy could be a useful intervention target for improving QoL among patients with CHB.…”
Section: Discussionsupporting
confidence: 52%
“…The main goal of CHB management is to improve patients’ survival rates and QoL. Patients with CHB usually suffer from a great burden due to the chronic nature of the illness, potentially severe complications, and discrimination in society, 4,6 which may have negative effects on their QoL. In Chen et al’s study, 7 patients with hepatitis B reported lower QoL compared to the general population.…”
Section: Quality Of Life Self-efficacy and Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Hierarchical nursing management was implemented based on the ability of nurses to obtain more satisfactory nursing services and better nursing quality. With reference to nurses' clinical experience and educational level, hospitals categorize and implement nursing tasks, optimize human resource allocation, and correctly construct and improve the specific content and process of nursing work, thereby enhancing nursing quality [8]. (4) A management system in line with nursing hierarchical management was established, and specific training programs and assessment standards and reasonable training and assessment systems were formulated based on the specific conditions of each department.…”
Section: Methodsmentioning
confidence: 99%
“…Even for high-risk patients with severe mental disorders, direct antiviral therapy had no effect on anxiety or depression during or after treatment for chronic hepatitis C infection ( Gallach et al, 2018 ). Kong et al (2021) showed that the incidence of anxiety increased in patients with chronic hepatitis B treated with oral antiviral therapy, and female gender and length of treatment were high risk factors. The incidence of anxiety and depression in patients with autoimmune hepatitis is also very high ( Schramm et al, 2014 ; Janik et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%